Zygmunt Ziembiński’s concept of the legal norm from a structuralist perspective - Bator, Andrzej (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
In the article I present the concept of the legal norm of conduct proposed by Zygmunt Ziembiński, situating it in the context of the structuralist research attitude – a methodological approach dominant in the Polish theory of law in the period when this key element of Ziembiński’s theory of law was created and shaped (the 1970s and 1980s). I illustrate individual fragments of the presented concept with selected quotations that are representative of the structuralist research approach. In my view, structuralism makes it possible to understand both the overwhelming influence of Ziembiński’s concept of the norm on the Polish legal theory of the second half of the twentieth century, as well as to explain the causes of the controversies that this concept provoked in some representatives of Polish jurisprudence. I also draw attention to the evolution of the concept in question, including the weakening of its structuralist overtones in the last years of the Professor’s scientific work. An example that exemplifies this tendency is the concept of competence norm.